Generalized polarizabilities and electroexcitation of the nucleon - Drechsel, D.; Kamalov, S. S.; Krein, G. [UNESP]; Pasquini, B.; Tiator, L. (Elsevier, 1999)
Generalized nucleon polarizabilities for virtual photons can be defined in terms of electroproduction cross sections as function of the 4-momentum transfer Q2. In particular, the sum of the generalized electric and magnetic polarizabilities ∑ = α + β and the spin polarizability γ can be expressed by virtual photon absorption cross sections integrated over the excitation energy. These quantities have been calculated within the framework of the recently developed unitary isobar model for pion photo- and electroproduction on the proton, which describes the available experimental data up to an excitation energy of about 1 GeV. Our results have been compared to the predictions of chiral perturbation theory. © 1999 Elsevier Science B.V. All rights reserved.
Keywords: Electroexcitation; Inelastic electron scattering; Nucleon polarizabilities; Spin content of the nucleon; Virtual compton scattering